Sex Differences in the Implementation of Character Education in Senior High Schools - Ipenas Amran Malin Mudo; Asmah Ahmad; Md. Rosli Ismail (Faculty of Teacher Training and Education, Universitas Terbuka, 2019)
Character education is the action and attitude of a person who reflects anything with good value. These values can be identified in his daily activities. Therefore, character education is considered very important as an effort to help someone to perceive or to understand and to act based on ethical or moral values. This purpose of this study is to analyze the implementation of character education in senior high schools (SMA) in Ujungbatu, Rokan Hulu Regency, Riau Province based on sex (male and female) differences. In order to answer the problems in the study, descriptive qualitative approach study is designed by using several methods namely interview, observation and documentation. The samples of the study were 339 students from three different high schools; they are SMA 1, SMA 2 and SMA Muhammadiyah. Finding of the study revealed that the four character education value, namely devotion, hard work, discipline, and honesty could be applied to both male and female Muslim and Christian students, and this is to indicate that these character values can be applied to the students. Finally, this character education method applies to students, especially in high school.